The Microstructure and Mechanical Behavior of TRIP 800 and DP 1000 Steels Welded by Electron Beam Welding Method - Sezgin, Cihangir Tevfik; Hayat, Fatih (FapUNIFESP (SciELO), 2020)
Abstract: TRIP 800 steel and DP 1000 steel welded by using the electron beam welding (EBW) method were investigated in this study. Martensite was a dominant phase at the fusion zone (FZ) of both steels. In addition, bainite and austenite were observed in the FZ of TRIP 800. The hardness of FZ and heat affected zone (HAZ) of both steels were higher than their base metals. The hardness of FZ of the TRIP 800 joinings was higher than the FZ of DP 1000. Ductility and tensile strength decreased at both of the joinings. However, this decrease became higher at the DP 1000 steel joinings compared to the TRIP 800 joinings. It was observed that the TRIP 800 joining absorbed more energy than the DP 1000 joining at impact notch test for each temperature.
Keywords: Dual phase steel; Microstructure; Transformation induced plasticity steel; Electron beam welding; Tensile strength; 7. Clean energy